Crop establishment and weed management effects on weed flora and yield of dry direct-seeded basmati rice (Oryza sativa) in the North-Western Indo-Gangetic plains - DHILLON, BUTA SINGH; KAUR, GURPREET; SHARMA, KANU PRIYA; RANDHAWA, RAMANJIT KAUR; SIDHU, NAVJOT; KUMAR, R MAHENDERA (The Indian Journal of Agricultural Sciences, 2026)
Despite the manifold advantages of dry direct-seeded rice (DSR), its adoption is constrained by severe weed infestation during the early stages of crop development. A field experiment was conducted during kharif 2021 and 2022 at Ludhiana, Punjab to evaluate the effect of crop establishment methods and weed management practices on weed dynamics, growth and yield of direct-seeded basmati rice (Oryza sativa L.). The experiment was laid out in a split-plot design with four crop establishment methods in main plots (broadcasting, line sowing, raised bed sowing on 1.0 m beds and raised bed sowing on 0.67 m beds) and four weed management practices in sub-plots {manual weeding, pendimethalin @ 0.75 kg/ha (pre-emergence) + bispyribac sodium @ 0.25 kg/ha (post-emergence), pendimethalin @ 0.75 kg/ha (pre-emergence) + manual weeding and mechanical weeding}. Line sowing significantly reduced sedge density while total weed dry matter was comparable under line sowing and bed sowing, which was significantly lower than broadcasting. Sequential application of pendimethalin followed by bispyribac sodium effectively reduced weed density and biomass and was comparable with pendimethalin followed by one manual weeding. Line-sowing and 1 m bed sowing methods produced significantly higher grain yield (4.02 and 3.93 t/ha during 2021 and 3.87 and 3.79 t/ha during 2022)  than 0.67 m bed and broadcasting. The study concluded that line sowing or 1 m bed sowing combined with sequential herbicide application is an effective and practical strategy for effective weed management and improving productivity of direct-seeded basmati rice under Punjab conditions.